The Effect Of Motivation And Coaching On The Implementation Of Patient Safety In Nurses With Responsive Culture As An Intervening Variable At Hospital X, Bekasi City - Kading, Indrawati Seska; Rini, Tjipto; Arrozie, MF (Teewan Solutions, 2025)
Patient safety is the right of every patient who receives health services in hospitals and is an indicator of improving the quality of services throughout the world. Patient safety includes all efforts made to prevent or minimize risks that could harm patients during the care, diagnosis or treatment process. The aim of this research is to analyze the direct and indirect influence of Motivation and Coaching on the Implementation of Patient Safety mediated by Responsive Culture. This research was conducted at the Hospital X. The research period is March 2024 – February 2025. This research approach uses a quantitative approach, with descriptive analysis methods that explain the relationship between variables. Using the Three Box Method, while analytics uses SEMPLS. The sampling technique used is Total Sampling. With a total of 162 nurses. Based on the results of the analysis, it shows that all Motivation dimensions are in the high category with an average index above 280. The Coaching variable for all dimensions is in the medium category with an average index ranging from 273 to 286. The Responsive Culture variable is in the medium category with an average index ranging from 273.46 to 284.57. The patient safety implementation variable for all dimensions is in the medium category with an index ranging from 277.16 to 284.57. The results of this research have implications for hospitals because implementing patient safety can improve the quality of service in hospitals. Responsive Culture is a culture that encourages nurses and other medical staff to be more sensitive to patient needs and responsive to safety issues. Good coaching will help nurses have better skills and knowledge regarding patient safety procedures.